Effect of pre-deformation before aging on discontinuous precipitation behaviour in Cu-Ni-Si alloys. (1st February 2021) - Cao, Yicheng; Han, Seung Zeon; Choi, Eun-Ae; Ahn, Jee Hyuk; Mi, Xujun; Huang, Guojie; Lee, Sangjin; Shin, Hyeonseok; Kim, Sangshik; Lee, Jehyun
ABSTRACT: The effect of deformation before aging on discontinuous precipitation in Cu–4.75wt%Ni–1.13wt%Si and Cu–6wt%Ni–1.42wt%Si alloys after solution treatment was investigated. Two kinds of deformation, one under and the other over the uniform deformation limit were implemented after solution treatment. With increasing deformation strain in both alloys, the discontinuous precipitation is accelerated and the aging time for a fully covered region by discontinuous precipitation is shortened. However, the Cu–6wt%Ni–1.42wt%Si alloy deformed under the uniform deformation limits showed an enhanced discontinuous precipitation compared to that for the alloy deformed over the uniform deformation limit. The deformation defects including dislocations and shear bands play the role of encouraging discontinuous precipitation. The shear bands formed during prior deformation beyond the necking point could provide sites for discontinuous precipitation initiation in the early stages of annealing However, shear bands tend to hinder the advance of discontinuous precipitation with further aging in the Cu–Ni–Si alloy with a high content of Ni and Si.